Increasing Polychaete diversity as a consequence of increasing research effort in Greek waters: new records and exotic species - SIMBOURA, N.; ZENETOS, A. (Mediterranean Marine Science, 2005)
The increasing diversity of the Greek Polychaete fauna over the last seven decades, as illustrated graphically, shows an increasing trend which is proportionately related to the research effort exerted. Ongoing research activities mainly in the depths of the N. Aegean Sea, as a result of which 13 new records have been added to the Greek Polychaete fauna, confirming the above statement. The new species records are presented along with their geographical distribution and habitat. According to the latest checklist of the Greek Polychaeta, 753 species of Polychaetes have been recorded in Greek waters. Finally, it should be noted that 6 Lessepsian migrants and 16 species have been recorded in the Mediterranean for the first time. Their distribution within Greece and worldwide is given and their presence in Greek waters is discussed.